2004
DOI: 10.2105/ajph.94.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and Mental Health: Understanding the Interactions Among Gender, Family Roles, and Social Class

Abstract: Understanding the effects of unemployment on mental health requires consideration of the interactions among gender, family responsibilities, and social class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
341
3
41

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(414 citation statements)
references
References 29 publications
29
341
3
41
Order By: Relevance
“…Our finding regarding the importance of employment status in relation to psychological morbidity is in keeping with previous findings suggesting the importance of work to both men's mental health and health behaviours (Lahelma, 1992;Artazcoz et al, 2004). The present study found that increased reporting of perceived barriers to PSA screening such as taking time off work is associated with higher levels of cancer-specific worry.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding regarding the importance of employment status in relation to psychological morbidity is in keeping with previous findings suggesting the importance of work to both men's mental health and health behaviours (Lahelma, 1992;Artazcoz et al, 2004). The present study found that increased reporting of perceived barriers to PSA screening such as taking time off work is associated with higher levels of cancer-specific worry.…”
Section: Discussionsupporting
confidence: 91%
“…A tendência de associação inversa entre escolaridade e risco de se tornar fumante foi mais modesta entre as mulheres quando comparadas aos homens, em aná-lise longitudinal 36 . Artacoz et al 37 , ao discutirem gênero, saúde e trabalho, mais especificamente o desemprego, creditam aos papéis socialmente atribuídos aos homens e às mulheres uma parte da explicação das diferenças observadas. Segundo os autores, para as mulheres, viver com cônjuge pode resultar em suporte financeiro e emocional, minimizando os efeitos do trabalho precário ou desemprego sobre a saúde e comportamentos relacionados; por outro lado, para os homens, essa mesma situação pode causar efeito reverso.…”
Section: Discussionunclassified
“…It emphasises a series of issues, including how prisoners feel unprepared for release, emotionally, practically and financially, and the difficulties they encounter when finding suitable accommodation and employment in the community. These issues have clear health implications, with inadequate and substandard housing having a direct (in terms of physical and mental health) and indirect (in relation to access to services) health impact (Gill and de Wildt 2003), and unemployment potentially being particularly detrimental to the mental health of men (Artazcoz et al 2004). …”
Section: Discussionmentioning
confidence: 99%